Efisiensi Penggunaan Protein pada Ayam Broiler dengan Pemberian Pakan Mengandung Tepung Daun Kayambang (Salvinia molesta) - Kurnia Andhika Sari; Bambang Sukamto; Bambang Dwiloka (Jurnal Agripet, 2014)
(Protein efficiency of broiler chickens fed with diets containing kayambang leaves meal)ABSTRACT The aim of the experiment was to determine the utilization of kayambang (Salvinia molesta) leaves meal until 18% based on its effects on protein consumption, protein intake, meat protein mass and protein efficiency ratio. One hundred broiler CP 707 day-old unsexed chicks, with an average body weight 502,48 6,99 g age 15 until 42 days. This study used a completely randomized design (CRD) with 4 treatments and 5 replications and each replication consisted of 5 chickens.. The treatments diets were T0 (basal diet), T1 (6% Salvinia molesta leaves meal), T2 (12% Salvinia molesta leaves meal), and T3 (18% Salvinia molesta leaves meal). The results showed that administration of Salvinia molesta leaf meal up to 18% level in the diet resulted in a decrease in the quality of the ration so that the protein utilization also decreased as indicated by the decline in the value of protein intake, protein intake, protein mass of meat and protein efficiency ratio.